Is the SSBN Deterrent Vulnerable to Autonomous Drones?. Issue 6 (1st November 2016) - Gates, Jonathan
Abstract : It has been claimed that drones, such as autonomous unmanned aerial vehicles and autonomous underwater vehicles, will be able to search the oceans for nuclear-powered submarines carrying nuclear-tipped weapons (SSBNs). Deployed in large numbers, it is posited that these drones would make the continuous at-sea deterrent obsolete. Jonathan Gates argues that few of the sensors carried by these drones would be able to detect a deeply submerged submarine, even if it were large. The range of these sensors, however sensitive, is very limited. Given the immense size of the submarines' potential operating area, the chance of detection is negligible, even if many drones were deployed. Despite this, there may still be a role for these drones in assisting anti-submarine forces to carry out their operations. This article considers these issues as they apply to the UK's SSBNs.